Systematic Review and Meta-Analysis of Utility of Graduated Compression Stockings in Prevention of Post-Thrombotic Syndrome. Issue 6 (June 2016) - Skervin, A.L.; Thapar, A.; Franchini, A.J.; Prandoni, P.; Shalhoub, J.; Davies, A.H.
Abstract : Background: Up to 50% of patients develop post-thrombotic syndrome (PTS) following their first proximal deep vein thrombosis (DVT). This meta-analysis aims to evaluate the effectiveness of graduated compression stockings (GCS) in preventing PTS. Method: Medline, Embase, Cochrane Database of Systematic Reviews, andClinicalTrials.gov were electronically searched from inception to January 2015 for studies investigating the effect of GCS in preventing PTS. All randomised control trials were considered for inclusion if they compared the efficacy of GCS (30–40 mmHg at the ankle) with either placebo or no stockings in adults with new proximal lower limb DVT. Methodological assessment, using the Cochrane Risk of Bias Tool, and data extraction was performed by two independent reviewers. The effect of GCS was expressed as the risk difference (RD). Results: A total of 686 articles were screened. Three randomised controlled trials inclusive of 1, 177 patients were eligible for inclusion. PTS developed in 49–70% of control patients at 5 years. High statistical heterogeneity was observed between trials (all PTS: I 2 = 0.94; severe PTS: I 2 = 0.79). The risk difference in PTS incidence between control and GCS arms varied from 0% to 39% between trials. In trials with a higher baseline prevalence of PTS, a visual trend towards more benefit with GCS was noted. Conclusion: Uncertainty because of sampling variability and heterogeneity was too high to conclude in favour or against an effect of wearing compression stockings in preventing PTS. An effect may be present for higher values of baseline risk. Further evidence is needed. Article history: